Sensitivity of octant of θ 23, CP violation and mass hierarchy in NOνA with multinucleon and detector effects - Paramita Deka; Kalpana Bora (Journal of High Energy Physics, 2024)
Abstract In this work, we investigate how multinucleon enhancement and RPA (Random Phase Approximation) suppression can affect the measurement of three unknown neutrino oscillation parameters — the CP-violating phase δ CP, the octant of the atmospheric mixing angle θ 23, and the determination of the mass hierarchy, in the appearance channel of the NOνA experiment. We include the presence of the detector effect as well in the analysis, which is crucial for capturing realistic experimental scenarios. We also conducted a comparison between the nuclear model Effective Spectral Function (calculated within the RFG model) with and without Transverse Enhancement in terms of sensitivity analysis. It is found that the analysis using our comprehensive model QE(+RPA)+2p2h along with Effective Spectral Function+Transverse Enhancement exhibits significantly enhanced sensitivity compared to the pure QE interaction process, in all the cases. Also, the higher octant of θ 23, the lower half plane of δ CP, and the normal mass hierarchy (HO-LHP-NH) exhibit improved sensitivity, enabling a more precise determination of the corresponding parameters. Furthermore, it is also noted that improving the performance of the detector also improves the results. Thus, including multinucleon effects and improving detector efficiency have the potential to enhance the capabilities of the NOνA (and other long baseline) experiment in conducting precise parameter studies.